ANALISIS KESULITAN BELAJAR MATEMATIKA DALAM MENYELESAIKAN SOAL CERITA PADA SISWA KELAS IV SEKOLAH DASAR NEGERI KUTAJAYA I KABUPATEN TANGERANG - Penta Agnayulia; Asep Suhendar; Asih Rosnaningsih (STKIP Subang, 2023)
The focus of this research is the causes of difficulties in learning mathematics in story problems in terms of difficulties in understanding the problem, errors in understanding concepts, technical errors in working and errors in drawing conclusions at SDN Kutajaya I. This research aims to analyze difficulties in learning mathematics in solving story problems in class students. IV at SDN Kutajaya I.. This research uses a descriptive qualitative method with data collection techniques in the form of observation, interviews, tests and documentation. The subjects in this research were teachers and students of class IV at the Kutajaya I State Elementary School, Tangerang Regency. After describing the data, the results of this research are: there are several types of student errors in solving story problems, including 12 errors in understanding the problem made by students with a percentage of 40%, conceptual errors made by students as many as 13 errors with a percentage of 43.3. %, there were 17 technical errors made by students with a percentage of 57%, and there were 30 errors in drawing conclusions made by students with a percentage of 100%.